Hermann und Margrit Rupf-Stiftung 2. - Kunstmuseum Bern, Bern (Bern : Kunstmuseum Bern, 1987)
Buri, Samuel ; Byars, James Lee ; Castallani, Enrico ; Chillida, Eduardo ; Eggenschwiler, Franz ; Fontana, Lucio ; Gerber, Theo ; Glattfelder, Hansjörg ; Graubner, Gotthard ; Iseli, Rolf ; Jensen, ALfred Julio ; Judd, Donald ; Kandinsky, Wassily ; Kermadec, Eugène de ; Léger, Fernand ; Lohse, Richard Paul ; Luginbühl, Bernhard ; etc.
boek